Diet and trophic structure in an assemblage of bats in montane forest of Pampa Hermosa National Sanctuary, Junin, Peru - Arias, Edith (2019)
We study the diet and trophic structure of 36 bat species from the Pampa Hermosa National Sanctuary. Faeces samples and gels with pollen were analyzed; seeds, pollen and remains of arthropods were found in the feces. Bats were classified in six functional groups. We found in the diet of the sedentary frugivores (FS), frugivorous nomads (FN) and nectarivores (N), 70 morphospecies of seed and pollen; in the diet of the aerial insectivorous (IA) and foliage gleaners (IR), nine morphospecies of arthropods. Principal component analysis shows the separation of bats and their diets; Carollia brevicauda-Piperaceae (Piper spp.), Vampyressa melissa-Moraceae (Ficus spp.), Sturnira lilium-Solanaceae; Anoura peruana and Anoura cultrata were separated by the consumption of Fabaceae and Bombacaceae, respectively, and Myotis spp. for the consumption of arthropods. The niche breadth was less than 0.50, in the assemblage. The values of dietary overlap were higher than 0.5, between: A. cultrata-A. caudifer (0.59), Sturnira lilium-Uroderma bilobatum (0.55), V. melissa-Platyrrhinus masu (0.62), in for the almost of AI and IR. The cluster analysis based on dietary overlap grouped to the strict frugivores Sternodermatinae in a different cluster than bats with insectivorous diets, as Carollia spp. and Anoura spp.